Teenagers and personalized digital advertising: When intrusion triggers resistance: An exploratory study - Naat, Wafa; Akrout, Wafa (International Transitions, 2025)
Equipped with new artificial intelligence technologies, companies now have the possibility of delivering personalized offers to meet consumers’ expectations and needs in a unique way through targeted or personalized advertising. This research treats the personalization of mobile advertising, which is now omnipresent in the browsing habits of young internet users. The massive use of smartphones by teenagers enables marketers to collect their data, more specifically via cookies, to refine their targeting. This qualitative study, carried out with 17 young teenagers, aims to understand advertising intrusion by taking account of the impact of personalization and advertising saturation on their ability to resist it. The results show that some teenagers believe that personalized advertising can sometimes be useful and interesting. However, this interest seems to be influenced by a perception of advertising invasion. The intrusion of advertising is perceived as a violation of privacy. As a result, these young teenagers do not hesitate to install software to avoid it, or even fully block it.